Strengthening the Branding of TKA ABA PCA Banguntapan Utara through the Optimization of English Language Skills and Entrepreneurship - Rofi, Muhammad Naufal Rofi; Mutiarin, Dyah; Sakir, Sakir; Khozin, Muhammad; Supriyani, Supriyani (Universitas Muhammadiyah Surakarta, 2025)
Aisyiyah Bustanul Athfal Kindergarten (TKA ABA) under the auspices of the North Banguntapan PCA, as an early childhood education institution based on religious values, is committed to developing a superior generation, with noble character, and competitiveness. However, competition in the education sector demands innovative strategies to strengthen the institution's competitiveness and identity. One such strategy is to integrate English and entrepreneurship skills into the curriculum. The problems faced are suboptimal human resources in English and a lack of understanding of entrepreneurship as a means of strengthening branding. The proposed solution is mentoring and training in English and entrepreneurship. The implementation method consists of four stages: preparation, implementation, monitoring and evaluation, and follow-up. The output of this service shows an increase in the ability of teachers in using English for learning and entrepreneurial skills for the purposes of institutional branding. The expected recommendations include follow-up by TKA ABA PCA to create an internal curriculum that combines English and entrepreneurship learning in real situations, the creation of a sustainable teacher learning community, and a commitment to establishing strategic partnerships with the business world and other educational institutions.